Exosomal MicroRNA-320a Derived From Mesenchymal Stem Cells Regulates Rheumatoid Arthritis Fibroblast-Like Synoviocyte Activation by Suppressing CXCL9 Expression - Meng, Qing; Qiu, Bing (Frontiers in Physiology, 2020)
Rheumatoid arthritis (RA), a chronic systemic inflammatory disease, is a primary cause of disability worldwide. The involvement of fibroblast-like synoviocytes (FLSs) in the regulation of the pathogenesis of RA has been highlighted. Mesenchymal stem cells (MSCs) are important candidates for cell-based treatment in many inflammatory autoimmune diseases. Herein we identify whether MSCs-derived exosomes loaded with microRNA-320a (miR-320a) regulate RA-FLSs. Synovial tissues from 22 patients with RA and 9 patients with osteoarthritis were collected respectively. RA-FLSs were obtained from patients with RA and their functions were evaluated by determining levels of Interleukin-1β (IL-1β), IL-6 and IL-8 and by Transwell migration and invasion assays. Dual luciferase reporter gene assays were employed to identify interaction between miR-320a and CXC chemokine ligand 9 (CXCL9). A co-culture system of MSCs-derived exosomes and RA-FLSs were performed. The collagen-induced arthritis (CIA) mouse models with arthritis and bone damage were developed. Our results revealed the existence of reciprocal expression of miR-320a and CXCL9 in the synovial tissues obtained from patients with RA. CXCL9 knockdown or miR-320a upregulation suppressed the activation, migration and invasion of RA-FLSs. CXCL9 was confirmed to be a target of miR-320a, and CXCL9 overexpression restored RA-FLS function in the presence of miR-320a. MSCs-derived exosomes containing miR-320a mimic significantly suppressed RA-FLS activation, migration and invasion in vitro, and attenuated arthritis and bone damage in mice with CIA in vivo. Our study uncovers that MSCs-derived exosomes participate in the intercellular transfer of miR-320a and subsequently inhibit the progression of RA. These results provide a novel potential therapeutic approach for RA treatment by increasing miR-320a in exosomes.